Valuable Ca/P Sources Obtained from Tuna Species’ By-Products Derived from Industrial Processing: Physicochemical and Features of Skeleton Fractions - Miriam López-Álvarez; Paula Souto-Montero; Salvador Durán; Sara Pérez-Davila; José Antonio Vázquez; Pío González; Julia Serra (Recycling)
The global tuna canning industry generates substantial volumes of by-products, comprising 50% to 70% of the total processed material. Traditionally, these by-products have been utilized in low-value products such as fish oils and fishmeal. However, there is significant potential to extract high-value compounds from these by-products, such as calcium phosphates (CaP), which can have pharmaceutical, agricultural and biotechnological applications. This work explores the potential of tuna canning by-products, particularly mineral-rich fractions (central skeleton, head and fish bones) as sources of calcium phosphates (CaP), offering a sustainable alternative to conventional synthetic derivatives within a circular bioeconomy framework. By-products from two of the most exploited species (yellowfin and skipjack) were subjected to enzymatic hydrolysis and chemical extraction, followed by controlled calcination to obtain CaP. The content of organic matter, nitrogen, total proteins, lipids and amino acids in the cleaned bones, as well as the main chemical bonds, structure and elemental composition (FT-Raman, XRD, XRF) were evaluated. Results indicated that the highest recovery yield of wet bones was achieved using the chemical method, particularly from the dorsal and caudal fins of yellowfin tuna. The proximal composition, with ash content ranging from 52% to 66% and protein content varying between 30% and 53%, highlights the potential of tuna skeleton substrates for plant growth formulations. Furthermore, variations in crystalline structures of the substrates revealed significant differences depending on the by-product source and species. XRD and Raman results confirmed a monophase calcium phosphate composition in most samples from both species, primarily based on hydroxyapatite (central skeleton, caudal and dorsal fin) or whitlockite/β-tricalcium phosphate (viscera), whereas the heads exhibited a biphasic composition. Comparing the species, yellowfin tuna (YF) exhibited a hydroxyapatite structure in the branchial arch and scales, while skipjack (SKJ) had a biphasic composition in these same regions.